The Effect of the Farmer’s Card Program in Managing Agricultural Business - Agoes Thony Ak; Yudhi Zuriah Wirya Purba (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Agriculture is an aspect that is quite important in improving the country's economy. With the increase in agricultural output, food yields will increase and be free from famine. However, the farmers experienced some difficulties in managing their agricultural business, such as the expensive price of fertilizer and the low selling price, so that the capital to turn the agricultural business into a frightening specter. Therefore, the government created a farmer card program to increase the yield of agricultural commodities. However, the farmer card program is still relatively young, so it is necessary to study the effect of the farmer card program in managing agricultural businesses. The purpose of this study is to determine the effect of the farmer's card, which is positive or negative so that it can contribute ideas for many parties. The method used is descriptive quantitative with the selection of respondents through purpose sampling which is adjusted to the research objectives with a total of 200 respondents. The results showed that the existence of a farmer card program had a positive influence in managing agricultural businesses. Unfortunately, not all farmers have farmer cards so that the price of subsidized fertilizer cannot be utilized by all farmers. Therefore, the government needs to increase the use of farmer cards by providing easy access to making farmer cards for all Indonesian farmers.